Allergy to betalactams and nucleotide‐binding oligomerization domain (NOD) gene polymorphisms. Issue 8 (29th July 2013) - Bursztejn, A. C.; Romano, A.; Guéant‐Rodriguez, R. M.; Cornejo, J. A.; Oussalah, A.; Chery, C.; Gastin, I.; Gaeta, F.; Barbaud, A.; Blanca, M.; Guéant, J. L.
Abstract: Background: Polymorphisms of interleukin genes related to IgE production and inflammation are predictors of hypersensitivity to betalactam, but nothing is known on the influence of NOD genes, despite their association with inflammation and atopy. Objective: To evaluate the association of NOD2 and NOD1 polymorphisms with betalactam allergy. Method: We genotyped 3 polymorphisms of NOD2 and 1 of NOD1 in 368 Italian and 387 Spanish patients, compared with 368 and 326 controls, respectively. Results: CT/TT genotypes of rs2066845 of NOD2 predicted a lower risk in Italy ( P  = 0.003), while WT/insC genotype of rs5743293 (also in leucine‐rich repeat domain) predicted a higher risk in Spain ( P  = 0.007). G allele of rs2066845 was associated with a higher level of IgE in the Italian population. Conclusion: The mirrored influence of these NOD2 polymorphisms on betalactam allergy in two populations suggests a link with pathways of inflammation and/or atopy through mechanisms, which need to be clarified.